Spatio-temporal dynamics of fish assemblage in the Datong and Xiaotong rivers, karst tributaries in the upper Yangtze River drainage: Implications for ecological adaptation and conservation of fish in rivers - Xiang, Peng; Wang, Xiaodong; Liu, Kan; Wu, Bo; Liang, Cong; Song, Zhaobin (Frontiers in Ecology and Evolution, 2022)
The Datong and Xiaotong rivers are karst tributaries in the upper Yangtze River drainage and represent considerable habitat diversity that contribute contribute to high fish diversity and rich fishery resources in the two rivers. During the few decades, fish resources have abruptly declined due to overfishing, water pollution and habitat degradation. In order to further strengthen conservation and restoration of fish resources and provide scientific support for fishery management in these rivers, the temporal and spatial dynamics of fish assemblage in the Datong and Xiaotong rivers were investigated in the present study. A total of 45 species were captured at 30 sample sites during four surveys conducted from March 2016 to January 2017. Species diversity and richness both increased from upstream to downstream in the two rivers. The fish assemblages significantly differed between river reaches, while did not differ in significant differences between four months. The spatial variations in the abundance of Rhynchocypris oxycephalus, Zacco platypus, Triplophysa bleekeri, Sinogastromyzon szechuanensis, Platysmacheilus nudiventris, Sinibrama taeniatus, Saurogobio gymnocheilus, Pseudorasbora parva, Pseudobagrus truncates and Opsariichthys bidens were considered to contribute most to the spatial pattern of fish assemblages. The lack of a temporal pattern of the fish assemblage in the rivers might be attributed to ecological habits of short-distance migration and diversified mesohabitats with riffles and pools for fish spawning, feeding or overwintering within a very short river range. Our results suggest the spatio-temporal dynamics of fish assemblages is highly adapted to the habitat characteristics in the two karst rivers. We recommend that fish conservation of these tributaries be focused on the mesohabitats, particularly the many pools and riffles.